Factors contributing to the poor acceptance of Malays towards Allianz Insurance Ipoh products. A study on marketing strategy / Norzaiha Izza Zainul Abidin Ahmad - Zainul Abidin Ahmad, Norzaiha Izza (2008)
Insurance is defined as the equitable transfer of the risk of a loss, from one entity to another, in exchange for a premium. An insurer is a company selling the insurance. The insurance rate is a factor used to determine the amount, called the premium, to be charged for a certain amount of insurance coverage. However, there are still a lot of problems that occur at all Insurance companies. This research is carried out to identify the issues that occur in this company. It is conducted to help identify the factors contributing to the poor acceptance of Malays towards Allianz Insurance Ipoh products. This is because the promotion and product itself is not attractive to the Malays. Besides that, Malays prefer to take Takaful that is based on Islamic system. Due to this matter, this research tries to identify the factors contributing to the poor acceptance of Malays towards Allianz Insurance Ipoh products. It hopes to identify and clarify whether there is a relationship or not between why are there lack of Malays taking insurance at Allianz Ipoh Branch with the promotion, price, place, product and the competitors of Allianz. This research will also identify the factors and measures taken by Allianz in the attempt to increase the number of Malay customers taking Allianz insurance.